Real time action recognition from video footage - Apon, Tasnim Sakib; Chowdhury, Mushfiqul Islam; Reza, MD Zubair; Datta, Arpita; Hasan, Syeda Tanjina (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.